Doktrin Keselamatan (Soteriologi) - Rossa Stevana; Tina Tina; Selvina Selvina; Sarmauli Sarmauli (Jurnal Magistra, 2024)
Salvation theology, or soteriology, is one of the fundamental doctrines in religious life. Every religion has a concept of salvation that answers questions about meaning, how to achieve it, as well as who saves and how someone can be saved. In the context of Christian theology, which is Trinitarian, soteriology is considered a development of creation theology. This doctrine emphasizes that salvation is a gift revealed by God as Savior from the beginning of creation. As part of theological studies, soteriology seeks to systematically explain the meaning of the human condition of being happy and good in unity with God after being free from any threat. Various concepts in the church tradition, such as grace, faith, justification, the church, the sacraments, and the saving work of Christ, play an important role in the understanding of salvation. With a broad scope, soteriology covers all aspects of human relationship with God.